Optimization of power system stabilizers using participation factor and genetic algorithm - Hassan, L.H.; Moghavvemi, M.; Almurib, H.A.F.; Muttaqi, K.M.; Ganapathy, V.G. (Elsevier, 2014)
This paper describes a method to determine the optimal location and the number of multi-machine power system stabilizers (PSSs) using participation factor (PF) and genetic algorithm (GA). The PF method is primarily used for number estimation and to identify the location of the PSSs, while the GA is applied to further reduce the number of PSSs, resulting in the optimization of their parameters and locations under different operating conditions. The problem is presented as a multi-objective optimization problem; maximizing the damping ratio of the electromechanical modes using different numbers of PSSs. The approach is successfully tested on the New England-New York interconnected system (16-machine and 68-bus), and its effectiveness in damping of local and inter-area modes of oscillations was proven. It is also compared to two other methods, which use only GA, in terms of damping ratio and computation time. In addition, the proposed approach demonstrates better performance compared to a fuzzy-based PSS when applied to the Iraqi National Super Grid System (INSGS).